A self-repairing high-gloss resin composition and its preparation method and use
By introducing self-healing polyurethane elastomer and compatibilizer into PC/ABS composite materials, the toughness and scratch resistance of the material are improved, and the problem of insufficient scratch resistance of the high-gloss PC/ABS resin materials is solved, achieving efficient Self-repair effect, suitable for automotive interior field.
Patent Information
- Application Number
- CN202210302289.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-03-24
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2042-03-24
AI Technical Summary
The existing high-gloss PC/ABS resin materials have insufficient scratch resistance in the automotive industry and cannot meet the scratch resistance standards requirements of the automotive industry. The existing self-repair methods are difficult to apply to large-volume polymer materials.
By introducing self-healing polyurethane elastomers and compatibilizers into PC/ABS composites, the toughness and scratch resistance of the material are improved, and its gloss and self-healing ability are improved through specific component proportions and process treatments.
It achieves good toughness and self-repairing performance without affecting gloss. The gloss retention rate exceeds 30% and the self-repairing rate exceeds 12%, which significantly improves the scratch resistance of the material and makes up for the tradition. Problem of insufficient scratch resistance of high-gloss PC/ABS resin.
Smart Images

Figure BDA0003563359800000031 
Figure BDA0003563359800000111 
Figure FDA0004864323320000011
Abstract
Description
Technical Field
[0001] The invention belongs to the field of composite materials, and in particular relates to a self-repairing high-gloss resin composition and a preparation method and application thereof. Background Art
[0002] With the improvement of people's living standards and the rapid development of the automobile industry, people have put forward higher requirements for the recycling of materials in the automotive field. Compared with interior materials that have been coated by electroplating, painting, film lamination, etc., direct injection molding materials are easier to recycle, which meets people's requirements for resource recycling. Secondly, it is environmentally friendly and low-carbon, which has a positive effect on the development of the automobile industry.
[0003] However, after the vehicle reaches the hands of consumers and begins to be used, the interior parts whose surfaces are not coated will be threatened by scratches and wear from time to time. For this reason, major automobile manufacturers have invested huge amounts of money and manpower to develop new scratch-resistant plastic resins. At present, there are three main methods to improve the scratch resistance of materials to achieve the surface of parts that are not easy to be scratched: (1) increase the hardness of the material itself to make it reach or approach the surface hardness of the sprayed parts; (2) reduce the friction coefficient of the surface of the material product; (3) improve the compatibility of the two-phase materials. However, these measures have not fundamentally solved the problem and can only alleviate the damage caused by scratches to a certain extent. Once the surface of such plastic parts is damaged, it will be permanent damage and cannot be repaired. New parts can only be replaced. Therefore, the development of a self-repairing and scratch-resistant polymer composite material is the only way to solve the above problems. The resulting composite material not only needs to have the scratch resistance of conventional scratch-resistant resin materials, but also needs to be able to self-repair the damaged parts under certain conditions to avoid appearance defects caused by defects.
[0004] Polycarbonate (PC) has become the general engineering plastic with the fastest production growth rate among the five major engineering plastics due to its advantages of high strength, high impact and wide operating temperature range. Acrylonitrile-butadiene-styrene copolymer (ABS) material also has impact resistance, chemical resistance and excellent electrical properties. It also has the advantages of easy processing, stable product size and good surface gloss. High-gloss PC / ABS resin, as a spray-free environmentally friendly green material, has also been gradually applied to the automotive field. However, the scratch resistance of PC / ABS is poor and cannot be compared with the scratch resistance of painted parts. It is difficult to meet the scratch resistance standard requirements of the automotive industry for parts. Therefore, the research and development of scratch-resistant self-repairing high-gloss PC / ABS resin materials is of practical and important significance for its application in the automotive industry.
[0005] Existing self-repairing methods for polymer materials, such as a self-repairing method for thermoplastic polymer materials disclosed in CN106832372A, are self-repaired by placing a thermoplastic polymer material with cracks to be repaired in a closed steam chamber filled with solvent vapor. The solvent may be dichloromethane, chloroform, tetrahydrofuran, acetone or butanone, etc. The polymer material may be polycarbonate, ABS, polyvinyl butyral, polymethyl methacrylate, polystyrene, polyvinyl chloride, etc. The pressure in the steam chamber is 0.01-0.2MPa, the temperature is 20-100°C, and the self-repairing time is 1-30min. Although the above method can achieve a self-repairing rate of up to 80%, it is difficult to apply to the self-repair of large-volume polymer materials such as automobiles.
[0006] On the basis of the existing technology, technicians in this field need to blend and modify PC and ABS, and introduce new blending components therein, so that the resulting PC / ABS composite material has higher gloss and certain self-repairing ability, a synergistic enhancement effect of self-repairing and scratch resistance, and improves the processing performance of the composite material and reduces its production cost. Summary of the invention
[0007] In view of the deficiencies in the prior art, the purpose of the present invention is to provide a new PC / ABS composite material with higher gloss and certain self-repairing ability, so that the processing performance of the composite material can be improved and the production cost can be reduced.
[0008] To achieve this object, one of the objects of the present invention is to provide a self-repairing high-gloss resin composition, which comprises the following components by weight percentage:
[0009]
[0010] Among them, the weight percentage of PC resin can be 32wt%, 35wt%, 40wt%, 45wt%, 50wt%, 55wt%, 60wt%, 65wt%, 70wt% or 75wt%, etc., the weight percentage of ABS resin can be 22wt%, 25wt%, 28wt%, 30wt%, 34wt%, 38wt%, 42wt%, 46wt%, 50wt% or 56wt%, etc., the weight percentage of self-healing polyurethane elastomer can be 2.5wt%, 3wt%, 3.5wt%, 4wt%, 4.5wt%, 5wt%, 5.5wt%, 6wt%, 7wt% or 7.5wt%, etc., and the weight percentage of compatibilizer can be 2.5wt%, 3wt%, 3.5wt%, 4wt%, 4.5wt%, 5wt%, 5.5wt%, 6wt%, 7wt% or 7.5wt%, etc.
[0011] The present invention can simultaneously improve the toughness and scratch resistance of the obtained composite material by introducing a polyurethane elastomer with self-repairing ability into the PC / ABS material, so that the obtained composite material can achieve self-repair of damaged parts during heat treatment, thereby avoiding appearance defects caused by flaws in products made from the composite material of the present invention.
[0012] Preferably, the self-healing polyurethane elastomer is obtained by mixing a diol containing a disulfide bond with a polyurethane prepolymer and polymerizing them.
[0013] Preferably, the diol containing a disulfide bond is any one of 2,2'-dithiodiethanol, 2,2'-(ethylenedithio)diethanol, 3,6-dithia-1,8-octanediol, 1,4-dithia-2,5-diol, 3,7-dithia-1,9-nonanediol or 3,5-dithia-1,7-heptanediol, or a mixture of at least two thereof.
[0014] Those skilled in the art can select any type of PC and ABS resin according to actual needs. Preferably, the number average molecular weight of the PC resin is 15000-30000, for example, 16000, 17000, 18000, 19000, 20000, 21000, 22000, 23000, 24000, 25000, 26000, 27000, 28000 or 29000, etc.
[0015] Preferably, the polydispersity coefficient of the PC resin is 1.2 to 2, for example, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9 or 2.0.
[0016] Preferably, the number average molecular weight of the ABS resin is 100,000 to 150,000, for example, 105,000, 110,000, 115,000, 120,000, 125,000, 130,000, 135,000, 140,000, 145,000 or 148,000.
[0017] Since factors such as the polydispersity coefficient or molecular weight of PC and ABS have a certain influence on the fluidity of the polymer after blending, exceeding the above molecular weight range has a more obvious effect on the orientation and distribution of additives in the polymer, thereby reducing the hardness and scratch resistance of the polymer resin surface to a certain extent, the above molecular weight and polydispersity coefficient are further preferred.
[0018] Preferably, the ABS resin is obtained by bulk polymerization, emulsion polymerization or suspension polymerization.
[0019] Preferably, the compatibilizer is ethylene-methyl acrylate copolymer and / or styrene-maleic anhydride copolymer.
[0020] Preferably, calculated by weight percentage, the self-healing high-gloss resin composition also includes 2.0 to 8 wt% (for example, 2.0 wt%, 3.0 wt%, 4.0 wt%, 5.0 wt%, 6.0 wt%, 7.0 wt% or 8.0 wt%, etc.) of additives. Those skilled in the art can choose any additive suitable for resin modification according to actual needs.
[0021] Preferably, the auxiliary agent is any one of an antioxidant, a lubricant or a filler, or a mixture of at least two of them.
[0022] Preferably, the auxiliary agent consists of the following components in parts by weight:
[0023] 1-5 parts antioxidant
[0024] Lubricant 1-20 parts
[0025] 1 to 20 parts of filler.
[0026] Among them, the weight proportion of the antioxidant can be 1.5 parts, 2 parts, 2.5 parts, 3 parts, 3.5 parts, 4 parts, 4.5 parts or 4.8 parts, the weight proportion of the lubricant can be 3 parts, 5 parts, 7 parts, 9 parts, 11 parts, 13 parts, 15 parts, 17 parts or 19 parts, and the weight proportion of the filler can be 3 parts, 5 parts, 7 parts, 9 parts, 11 parts, 13 parts, 15 parts, 17 parts or 19 parts, etc.
[0027] Among the auxiliary agents, the antioxidant and the lubricant can be any commonly used auxiliary agents for resin modification. The content or type of the antioxidant and the lubricant has no obvious effect on the gloss, self-repairing and other properties of the obtained self-repairing high-gloss resin composition. Preferably, the antioxidant is any one of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, β-(4-hydroxy-3,5-di-tert-butylphenyl) propionate, 2,2-thiobis[ethyl 3-(3,5-di-dibutyl-4-hydroxyphenyl) propionate], dilauryl thiodipropionate or distearyl thiodipropionate, or a mixture of at least two of them.
[0028] Preferably, the lubricant is any one of ultra-high molecular weight polyethylene, olefin copolymer, polyethylene wax, polydimethylsiloxane or oleic acid amide, or a mixture of at least two thereof.
[0029] Preferably, the filler is the following resin filler that has been alkali washed:
[0030] Any one of mordenite, pyrophyllite, enstatite, mica or barite, or a mixture of at least two of them.
[0031] Preferably, the alkali washing treatment comprises the following steps:
[0032] The resin filler is mixed with the alkali metal hydroxide solution and stirred under the action of ultrasonic dispersion.
[0033] The surface of the resin filler after alkali washing contains active hydroxyl groups, which has higher surface compatibility with the resin matrix, can improve the dispersibility and action of the filler in the melt, ensure that the filler can be firmly anchored in the melt, and can further improve the scratch resistance, gloss retention and notched impact strength of the obtained composite material.
[0034] The second object of the present invention is to provide a method for preparing the self-repairing high-gloss resin composition, the preparation method comprising the following steps:
[0035] The PC resin, ABS resin, self-repairing polyurethane elastomer and compatibilizer in the formula amount are mixed to obtain a mixture, and then the mixture is placed in an extruder for mixing and extrusion to obtain the self-repairing high-gloss resin composition.
[0036] Preferably, an auxiliary agent is also added to the mixture.
[0037] Preferably, the mixing and extruding temperature is 225-265°C, for example, 225°C, 230°C, 235°C, 240°C, 245°C, 250°C, 255°C, 260°C or 265°C.
[0038] Preferably, the extruder is provided with ten extrusion sections, and the temperature of each extrusion section is set as follows:
[0039] The temperature of the first section is 220℃, the temperature of the second section is 230℃, the temperature of the third section is 240℃, the temperature of the fourth section is 250℃, the temperature of the fifth section is 255℃, the temperature of the sixth section is 255℃, the temperature of the seventh section is 255℃, the temperature of the eighth section is 255℃, the temperature of the ninth section is 255℃, and the temperature of the tenth section is 250℃.
[0040] The third object of the present invention is to provide an application of the self-repairing high-gloss resin composition in automobile interior decoration.
[0041] The numerical range described in the present invention not only includes the point values listed above, but also includes any point values between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0042] Compared with the prior art, the present invention has the following beneficial effects:
[0043] The present invention introduces a compatibilizer and a self-repairing polyurethane elastomer into the PC / ABS composite material, thereby being able to give the composite material good toughness and excellent self-repairing performance without affecting the gloss of the composite material. The self-repairing high-gloss resin composition obtained by the present invention has a gloss of more than 90GU, a gloss retention rate of more than 30%, a self-repairing rate after scratching of more than 12%, good scratch resistance, and multiple utilization of plasticizers, thereby making up for the problem of insufficient scratch resistance of traditional high-gloss PC / ABS resins. The present invention is a truly spray-free high-gloss material and has broad application prospects in the field of automotive interiors. DETAILED DESCRIPTION
[0044] The technical solution of the present invention is further illustrated below through specific implementation methods.
[0045] Example 1
[0046] The self-repairing high-gloss resin composition 1 was prepared by the following method:
[0047] 62 kg of PC resin with a number average molecular weight of 15000 g / mol, a polydispersity coefficient of 1.85 and a glass transition temperature of 138°C, 23 kg of ABS resin obtained by bulk polymerization with a number average molecular weight of 100000 g / mol, 4.5 kg of self-repairing polyurethane elastomer, 7.5 kg of a copolymer of compatibilizer styrene and maleic anhydride, 0.3 kg of an antioxidant 2,2-thiobis[3-(3,5-dibutyl-4-hydroxyphenyl)ethyl propionate], 1.2 kg of a lubricant liquid olefin copolymer and 1.5 kg of a filler are mixed to obtain a mixture, and then the mixture is placed in an extruder for mixing and extrusion to obtain the self-repairing high-gloss resin composition 1.
[0048] The self-healing polyurethane elastomer is prepared by the following method: 6 parts by mass of 3,6-dithiazole-1,8-octanediol is dissolved in DMSO as a chain extender, 25 parts by mass of a polyurethane prepolymer containing an isocyanate group and having a molecular weight of 3000 is added thereto, and after reacting at 60° C. for 12 hours, the reaction product is soaked and washed with deionized water, and the self-healing polyurethane elastomer is obtained after freeze-drying.
[0049] The filler is prepared by the following method: mixing flaky mordenite with a sodium hydroxide solution with a concentration of 1 mol / L, ultrasonically dispersing the mixed solution for 12 hours, filtering the mixed solution, and washing and drying the filter residue to obtain the filler.
[0050] The extruder is a ZSK-26Mc twin-screw extruder produced by Coperion, Germany, which is provided with ten extrusion sections, and the temperature of each extrusion section is set as follows:
[0051] The temperature of the first section is 210℃, the temperature of the second section is 230℃, the temperature of the third section is 240℃, the temperature of the fourth section is 250℃, the temperature of the fifth section is 255℃, the temperature of the sixth section is 255℃, the temperature of the seventh section is 255℃, the temperature of the eighth section is 255℃, the temperature of the ninth section is 255℃, and the temperature of the tenth section is 250℃.
[0052] Example 2
[0053] The only difference from Example 1 is that the amount of PC resin added is 66 kg, the amount of self-repairing polyurethane elastomer added is 2 kg, and the amount of compatibilizer added is 6 kg. Example 2 obtains a self-repairing high-gloss resin composition 2.
[0054] Example 3
[0055] The only difference from Example 1 is that the amount of PC resin added is 64 kg, the amount of self-repairing polyurethane elastomer added is 8 kg, and the amount of compatibilizer added is 2 kg. Example 3 obtains a self-repairing high-gloss resin composition 3.
[0056] Example 4
[0057] The only difference from Example 1 is that the amount of PC resin added is 30 kg, and the amount of ABS resin added is 55 kg. Example 4 obtains a self-repairing high-gloss resin composition 4.
[0058] Example 5
[0059] The only difference from Example 1 is that the amount of PC resin added is 30 kg, the amount of ABS resin added is 60 kg, the amount of self-repairing polyurethane elastomer added is 2 kg, and the amount of compatibilizer added is 5 kg. Example 5 obtains a self-repairing high-gloss resin composition 5.
[0060] Example 6
[0061] The only difference from Example 1 is that the number average molecular weight of the PC resin is 30,000 g / mol, the polydispersity coefficient is 1.98, and the number average molecular weight of the ABS resin is 150,000, which is obtained by emulsion polymerization. Example 6 obtains a self-repairing high-gloss resin composition 6.
[0062] Example 7
[0063] The only difference from Example 1 is that the compatibilizer is ethylene-methyl acrylate copolymer. Example 7 obtains a self-repairing high-gloss resin composition 7.
[0064] Example 8
[0065] The only difference from Example 1 is that the amount of lubricant added is 0.7 kg and the lubricant is ultra-high molecular weight polyethylene, the amount of filler added is 2 kg and the filler is prepared by the following method:
[0066] The flaky enstatite is mixed with a sodium hydroxide solution with a concentration of 1 mol / L, and the mixed solution is ultrasonically dispersed for 12 hours. The mixed solution is then filtered, and the filter residue is washed with water and dried to obtain the filler.
[0067] Example 8 obtains a self-repairing high-gloss resin composition 8.
[0068] Example 9
[0069] The only difference from Example 1 is that the amount of antioxidant added is 0.2 kg and the antioxidant is pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, the amount of lubricant added is 0.2 kg and the lubricant is oleamide, and no filler component is added.
[0070] Example 9 obtains a self-repairing high-gloss resin composition 9.
[0071] Comparative Example 1
[0072] The only difference from Example 1 is that no self-healing polyurethane elastomer component is added.
[0073] Comparative Example 1 obtained a resin composition 10.
[0074] Comparative Example 2
[0075] The only difference from Example 1 is that no compatibilizer component is added.
[0076] Comparative Example 2 obtained resin composition 11.
[0077] Comparative Example 3
[0078] The only difference from Example 1 is that the added amount of the self-healing polyurethane elastomer component is 12 kg.
[0079] Comparative Example 3 obtained resin composition 12.
[0080] Comparative Example 4
[0081] The only difference from Example 1 is that the amount of the compatibilizer component added is 12 kg.
[0082] Comparative Example 4 obtained resin composition 13.
[0083] The resin compositions 1 to 13 obtained in the above-mentioned embodiments and control examples were characterized and tested by the following test methods. The test results are listed in Table 1.
[0084] (1) Glossiness test
[0085] Resin compositions 1 to 14 were respectively injection molded into test specimens with a size of 110 mm × 100 mm × 2.5 mm. According to the method described in the international standard ISO 2813-2014 "Determination of specular gloss of non-metallic paint films of paints and varnishes at 20°, 60° and 85°", the gloss of the above test specimens at 20° was tested using a gloss meter.
[0086] (2) Gloss retention test
[0087] According to the method described in the industry standard PV 3987 "Scratch resistance of high-gloss surfaces of vehicle interiors", a scratch test was performed on the surface of each test sample in the gloss test using a 249 scratch hardness tester produced by Erichsen, Germany. Afterwards, a gloss meter was used to test the gloss of the test samples after the scratch test at 20°, and the gloss retention rate of each test sample was calculated. The higher the gloss retention rate, the better the scratch resistance.
[0088] (3) Scratch resistance test
[0089] According to the method described in the industry standard PV 3952 "Scratch Resistance Test", the 430P electric cross-hatch tester produced by Erichsen of Germany was used to conduct a 100-grid scratch resistance test on the surface of each test sample in the gloss test. Then, the L, A and B values of each test sample before and after the scratch resistance test were tested using a KONICA MINOLTA colorimeter. △E was calculated according to the formula in the industry standard PV 3952. 1 , △E 1 The smaller the value, the better the scratch resistance.
[0090] (4) Self-repair rate experiment
[0091] Place the test sample after the scratch resistance test in a blast drying oven at 80°C for 2 hours, and use a colorimeter to test the L, A and B values of the heated test sample again, and calculate △E 2 , self-repair rate = [(△E 2 -△E 1 ) / △E 1 ]×100%, the higher the self-repair rate, the better the self-repairability.
[0092] (5) Notched impact strength test
[0093] According to the method described in the international standard ISO179-1993 "Determination of impact strength of plastics - simply supported beam", the Izod notched impact strength of composite materials 1 to 13 was tested respectively.
[0094] Table 1 Performance comparison of resin compositions 1 to 13
[0095]
[0096] From the comparison between Example 1 and Examples 1 to 8, it can be seen that by appropriately adjusting the addition amount, molecular weight and component type of each component in the resin composition, a self-repairing high-gloss resin composition with good scratch resistance having a gloss of more than 70GU, a gloss retention rate of >30%, and a self-repair rate after scratching of >12% can be obtained according to demand.
[0097] From the comparison between Example 1 and Example 8 and Example 9, it can be seen that after the alkali-washed filler is introduced into the resin composition, the glossiness of the surface does not change significantly, but the scratch resistance, gloss retention and notched impact strength are significantly improved.
[0098] From the comparison between Example 1 and Control Examples 1 to 4, it can be seen that if the resin composition lacks a self-healing elastomer or a compatibilizer component, or when any of the above components is added in excessive amounts, the self-healing performance, gloss retention rate and scratch resistance of the obtained resin composition will be significantly reduced.
[0099] In summary, the present invention introduces a compatibilizer and a self-repairing polyurethane elastomer into the PC / ABS composite material, thereby being able to give the composite material good toughness and excellent self-repairing performance without affecting the gloss of the composite material. The self-repairing high-gloss resin composition obtained by the present invention has a gloss of more than 90GU, a gloss retention rate of more than 30%, a self-repairing rate after scratching of more than 12%, good scratch resistance, and realizes multiple utilization of plasticizers, making up for the insufficient scratch resistance of traditional high-gloss PC / ABS resins, and obtaining a truly spray-free high-gloss material, which has broad application prospects in the field of automotive interiors.
[0100] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.
Claims
1. A self-repairing high-gloss resin composition, characterized in that: Calculated by weight percentage, the self-repairing high-gloss resin composition includes the following components: The self-repairing polyurethane elastomer is obtained by mixing a diol containing a disulfide bond with a polyurethane prepolymer and polymerizing the mixture; The diol containing a disulfide bond is any one of 2,2'-dithiodiethanol, 2,2'-(ethylene dithio)diethanol, 3,6-dithia-1,8-octanediol, 1,4-dithia-2,5-diol, 3,7-dithia-1,9-nonanediol or 3,5-dithia-1,7-heptanediol, or a mixture of at least two thereof; The compatibilizer is ethylene-methyl acrylate copolymer and / or styrene-maleic anhydride copolymer.
2. The self-repairing high-gloss resin composition according to claim 1, characterized in that: The number average molecular weight of the PC resin is 15,000 to 30,000.
3. The self-repairing high-gloss resin composition according to claim 1, characterized in that: The polydispersity coefficient of the PC resin is 1.5-2.
4. The self-repairing high-gloss resin composition according to claim 1, characterized in that: The number average molecular weight of the ABS resin is 100,000 to 150,000.
5. The self-repairing high-gloss resin composition according to claim 1, characterized in that: The ABS resin is obtained by bulk polymerization, emulsion polymerization or suspension polymerization.
6. The self-repairing high-gloss resin composition according to claim 1, characterized in that: Calculated by weight percentage, the self-repairing high-gloss resin composition also includes 2.0 to 8.0 wt % of auxiliary agents.
7. The self-repairing high-gloss resin composition according to claim 6, characterized in that: The auxiliary agent is any one of an antioxidant, a lubricant or a filler, or a mixture of at least two of them.
8. The self-repairing high-gloss resin composition according to claim 7, characterized in that: The auxiliary agent is composed of the following components in parts by weight: 1-5 parts of antioxidant Lubricant 1-20 parts 1 to 20 parts of filler.
9. The self-repairing high-gloss resin composition according to claim 7, characterized in that: The antioxidant is any one of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, octadecylβ-(4-hydroxy-3,5-di-tert-butylphenyl)propionate, 2,2-thiobis[ethyl 3-(3,5-di-dibutyl-4-hydroxyphenyl)propionate], dilauryl thiodipropionate or distearyl thiodipropionate, or a mixture of at least two of them.
10. The self-repairing high-gloss resin composition according to claim 7, characterized in that: The lubricant is any one of ultra-high molecular weight polyethylene, olefin copolymer, polyethylene wax, polydimethylsiloxane or oleic acid amide, or a mixture of at least two of them.
11. The self-repairing high-gloss resin composition according to claim 7, characterized in that: The filler is the following resin filler which has been subjected to alkali washing treatment: any one of mordenite, pyrophyllite, enstatite, mica or barite, or a mixture of at least two of them.
12. The self-repairing high-gloss resin composition according to claim 11, characterized in that: The alkali washing treatment comprises the following steps: The resin filler is mixed with the alkali metal hydroxide solution and stirred under the action of ultrasonic dispersion.
13. A method for preparing the self-repairing high-gloss resin composition according to any one of claims 1 to 12, characterized in that: The preparation method comprises the following steps: The PC resin, ABS resin, self-repairing polyurethane elastomer, compatibilizer, auxiliary agent and filler in the formula amount are mixed to obtain a mixture, and then the mixture is placed in an extruder for mixing and extrusion to obtain the self-repairing high-gloss resin composition.
14. The preparation method according to claim 13, characterized in that: Auxiliary agents are also added to the mixture.
15. The preparation method according to claim 13, characterized in that: The temperature of the mixing and extruding is 225-265°C.
16. The preparation method according to claim 13, characterized in that: The extruder is provided with ten extrusion sections, and the temperature of each extrusion section is set as follows: The temperature of the first section is 210℃, the temperature of the second section is 230℃, the temperature of the third section is 240℃, the temperature of the fourth section is 250℃, the temperature of the fifth section is 255℃, the temperature of the sixth section is 255℃, the temperature of the seventh section is 255℃, the temperature of the eighth section is 255℃, the temperature of the ninth section is 255℃, and the temperature of the tenth section is 250℃.
17. Use of the self-repairing high-gloss resin composition according to any one of claims 1 to 12 in automobile interior decoration.
